Simulations to Improve Circular Loop Antenna Characteristics at the Frequency of 1.42 GHz using Window Functions - Jallod, Uday E.; Ibrahim, Rasha H.; Abood, Kamal M. (Iraqi Journal of Science, 2026)
This study is focused on simulations of the radiation pattern characteristics for a circular loop antenna that operates at a frequency of 1.42 GHz (λ = 21 cm). The circular loop antenna pattern is considered weak and depends on the antenna's circumference. Therefore, five values of antenna circumferences are chosen to achieve the best results for the antenna characteristics. These circumferences are taken to be smaller, equal, and larger than the operated wavelength. Then, the antenna characteristics are estimated. These characteristics are antenna directivity, effective area, efficiency, and solid angle, which are found to be 2.6, 0.009 (m2), 0.011, and 11.5 (radian), respectively. To improve these characteristics, four types of window functions are implemented by their multiplication with the Fourier transform of the circular loop antenna pattern. These window functions are rectangular window, Hanning Window, Hamming Window, and Kaiser Window. The promising results are obtained via the Hanning window since it gives acceptable values for antenna characteristics. These values are found to be (directivity = 100), (effective area = 0.35 m2), (efficiency = 0.6), and (solid angle = 0.1 radian). Overall, the encouragement results are obtained by a small circular loop antenna, especially at a circumference less than the operated wavelength.